Philosophy and the Problem of God in Xavier Zubiri - Vargas, Esteban (Pensamiento. Revista de Investigación e Información Filosófica, 2015)
This paper attempts to clarify what constitutes «the problem of God» as a philosophical problem with Xavier Zubiri. To do this, we divide the paper into three parts. First, we should clarify if possible to study «philosophically» the subject of «God». From Zubiri, this is possible if we study the «problem» of God as something «given» sentiently, not «God» understood as a supreme being beyond the world. Second, we have to analyze what is the «problem of God» according to Zubiri. Do we mean that the problem of God is «given» as a starting point in the primordial apprehension? Or might it be that the «problem of God» is something that can lead or not «towards» God? Finally, thirdly, we must analyze the various attitudes and solutions to the «problem of God» as atheism, agnosticism or theism. Zubiri defended himself a theistic position and established a rational proof that was gradually modified in his later years.